Simulação computacional da extração líquido-líquido fracionada de enzimas para produção de biodiesel - Meneghine, Aylan Kener [UNESP]; Oliveira, Leonardo Hadlich de; Monteiro Filho, Elias de Souza [UNESP] (My University, 2012)
Liquid-liquid extraction is utilized for purification of biomolecules by Aqueous Biphasic Systems (ABS), since this process does not damage the biotechnological potential of these compounds. In this work, using the free software Scilab®, the fractionated liquid-liquid extraction was studied aiming a lipase (target enzyme) partition in a water + PEG + DEX system. Lisozime was considered as contaminant. As computer simulations has been extensively used when a first estimation of technical feasibility of process is desired, this work demonstred that the system is viable for recovery the 80 % till 90 % the target enzyme, but should be noted that the trial aimed only the fractionation of the enzyme target of a contaminant, not its concentration, which should be done by another process.
Computer simulation of liquid-liquid extraction of enzymes fractionated to produce biodiesel
Keywords: Biocombustíveis; Engenharia de Bioseparações; extração líquido-líquido; simulação; Lipase; Transesterification